2010
DOI: 10.1007/s00226-010-0344-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyvinyl alcohol on leachability and efficacy of boron wood preservatives against fungal decay and termite attack

Abstract: In this study, the use of polyvinyl alcohol (PVA) as boron fixative agent was investigated. Two levels of PVA (2.5 and 4%) were evaluated with disodium octaborate tetrahydrate (DOT) at three concentrations (1, 2 and 4% boric acid equivalent (BAE)) using a double vacuum impregnation process on Scots pine sapwood specimens. Leaching was performed according to a laboratory leaching procedure. Boron analysis using atomic absorption spectrometer showed a significant reduction in boron leachability for the samples t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…APP and boron compounds retard flame by producing carbona-ceous foam which protects the material from temperature rise (Kurt and Mengeloglu 2011). Boron compounds, such as disodium octaborate tetrahydrate (DOT), boric acid and borax are odourless, colourless, non-corrosive, cheap and non-toxic chemicals (Mohareb et al 2011). However, the leaching of boron compounds from wood has been one of the significant problems for over years.…”
Section: Introductionmentioning
confidence: 99%
“…APP and boron compounds retard flame by producing carbona-ceous foam which protects the material from temperature rise (Kurt and Mengeloglu 2011). Boron compounds, such as disodium octaborate tetrahydrate (DOT), boric acid and borax are odourless, colourless, non-corrosive, cheap and non-toxic chemicals (Mohareb et al 2011). However, the leaching of boron compounds from wood has been one of the significant problems for over years.…”
Section: Introductionmentioning
confidence: 99%
“…Inorganic boron compounds used in outdoor exposures have to be modified with fixatives or with water repellents, polymerizable monomers or other protective additives to reduce their leachability (Babuder et al 2004, Lloyd et al 2001. Polyvinyl alcohols belong to the most known fixatives which form stable complex with the borate ions (Mohareb et al 2010a). Complexes with boron create also tannins (Pizzi & Baecker 1996).…”
Section: The Most Used Fungicides For Wood Protectionmentioning
confidence: 99%
“…PVA has a broad range of applications in the medical, 9 agricultural, 10,11 industrial, 12 and manufacturing industries. In addition, PVA is also used in the construction industry as a building binder, a cement-based composite material modifier, a fiber reinforcement, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…PVA has a broad range of applications in the medical, agricultural, , industrial, and manufacturing industries. In addition, PVA is also used in the construction industry as a building binder, a cement-based composite material modifier, a fiber reinforcement, and so on. It can significantly increase the fracture energy and improve the cracking problems of cement-based materials. , Kou evaluated the effect of PVA on the durability of recycled aggregate concrete and found that the introduction of PVA can reduce the water absorption of the matrix, thereby enhancing the resistance to chloride ion penetration.…”
Section: Introductionmentioning
confidence: 99%